Washington View: 3 ways Congress can support public education. (November 2017) - Ferguson, Maria
Some of education secretary Betsy DeVos's policy positions — particularly her advocacy for school choice and her decision to limit her department's regulatory stance — are out of step with public opinion. A bipartisan response from Congress would be welcome on at least three important issues: protecting DACA (Deferred Action for Childhood Arrivals), providing strong oversight of for-profit colleges, and defining a strong federal commitment to public education .